Operationalising outpatient antimicrobial stewardship to reduce system-wide antibiotics for acute bronchitis. Issue 3 (1st July 2021) - Johnson, Morgan Clouse; Hulgan, Todd; Cooke, Robin G; Kleinpell, Ruth; Roumie, Christianne; Callaway-Lane, Carol; Mitchell, Lauren D; Hathaway, Jacob; Dittus, Robert; Staub, Milner
Abstract : Background: Antibiotics are not recommended for treatment of acute uncomplicated bronchitis (AUB), but are often prescribed (85% of AUB visits within the Veterans Affairs nationally). This quality improvement project aimed to decrease antibiotic prescribing for AUB in community-based outpatient centres from 65% to <32% by April 2020. Methods: From January to December 2018, community-based outpatient clinics' 6 months' average of prescribed antibiotics for AUB and upper respiratory infections was 63% (667 of 1054) and 64.6% (314 of 486) when reviewing the last 6 months. Seven plan–do–study–act (PDSA) cycles were implemented by an interprofessional antimicrobial stewardship team between January 2019 and March 2020. Balancing measures were a return patient phone call or visit within 4 weeks for the same complaint. Χ 2 tests and statistical process control charts using Western Electric rules were used to analyse intervention data. Results: The AUB antibiotic prescribing rate decreased from 64.6% (314 of 486) in the 6 months prior to the intervention to 36.8% (154 of 418) in the final 6 months of the intervention. No change was seen in balancing measures. The largest reduction in antibiotic prescribing was seen after implementation of PDSA 6 in which 14 high prescribers were identified and targeted for individualised reviews of encounters of patients with AUB with an antimicrobial steward. Conclusions: Operational implementation of successful stewardship interventions is challenging and differs from the traditional implementation study environment. As a nascent outpatient stewardship programme with limited resources and no additional intervention funding, we successfully reduced antibiotic prescribing from 64.6% to 36.8%, a reduction of 43% from baseline. The most success was seen with targeted education of high prescribers.